Temporal distribution characteristics of earthquakes in Taiwan, China - Xu, Weijin; Li, Xuejing; Gao, Mengtan (Frontiers in Earth Science, 2023)
The seismic temporal distribution characteristics is an important basis for earthquake prediction and seismic hazard analysis. In this paper, based on the seismic catalogue in Taiwan, with Exponential distribution model, the Gamma distribution model, Weibull distribution model, the Logarithmic normal distribution model and Brownian passage time distribution (BPT) model for the target models, the maximum likelihood method is adopted to estimate the model parameters. According to the Akaike Information Criterion (AIC), Bayesian Information Criterion (BIC) and K-S test to determine the optimal model that can describe the temporal distribution of earthquakes in Taiwan. The results show that for earthquakes with moderate-strong magnitude (M<7.0), the Gamma distribution model can well describe the temporal distribution characteristics of earthquakes. While large earthquakes (M≥7.0) can be described entirely by Exponential distribution. In addition, the temporal correlation between earthquakes is also studied by diffusion entropy analysis method. The results show that seismic activity has temporal correlation, and earthquakes with relatively small magnitude (M<7) are affected by larger earthquakes (M≥7.0), thus showing the long-term memory in time. In this study, we also calculated the probability of the occurrence of a major earthquake in Taiwan. The results show that the probability of an earthquake with a magnitude of more than 7.0 in Taiwan in the next 10 years can reach 91.3%.The results of this paper have important reference value for the selection of seismic time distribution model and the calculation of seismic activity parameters in earthquake prediction and seismic hazard calculation, and have important scientific significance for understanding the mechanism of earthquake genesis.